ANALISIS WACANA KRITIS SARA MILLS TERHADAP CERPEN “RABIAH” KARYA HASAN AL BANNA - Agape Viandasari Sinaga; Alpiani Br. Tarigan; Ayu Angely Br. Galingging; Della Putri Rahmadani5; Lasenna Siallagan; Rezki Antonio F. Ginting; Syifa Hayati (FKIP, Universitas Palangka Raya, 2023)
This research aims to analyse the image of women in the short story entitled “Rabiah” by Hasan Al Banna. This research used descriptive qualitative method. The subject of this research is short story entitled “Rabiah” by Hasan Al Banna. The data of this research are words, phrases, or sentences that contain information about the image of women in the short story entitled “Rabiah” by Hasan Al Banna. The data were collected by reading and note-taking techniques. The data obtained from this study were analysed using content analysis. Based on the analysis result, it was found that a woman in the short story entitled “Rabiah” by Hasan Al Banna described as a brave, intelligent, and kind woman. A brave woman was described through the figure of Rabiah who has bravery to work in the overseas without her family. An intelligent woman was described through the figure of Rabiah who showed her ability to think perfectly. A kind woman was described through the figure of Rabiah who respected her parents by listening their advice.